Long-Term Persistence and Relevant Therapeutic Impact of High-Titer Viral-Neutralizing Antibody in a Convalescent COVID-19 Plasma Super-Donor: A Case Report - De Rienzo, Mafalda; Foddai, Maria Laura; Conti, Laura; Mandoj, Chiara; Iaboni, Stefano; Saladini, Ilenia; Castilletti, Concetta; Matusali, Giulia; Donno, Davide Roberto; Marchioni, Luisa; Ianniello, Stefania; Corpolongo, Angela; et al. (Frontiers in Immunology, 2021)
A convalescent, non-severe, patient with COVID-19 was enrolled as a hyper-immune plasma voluntary donor by the Immuno-Hematology and Transfusion Unit of the Regina Elena National Cancer Institute in Rome, under the TSUNAMI national study criteria. Material and methods: During a nearly 6-month period (May–October 2020), the patient was closely monitored and underwent four hyperimmune plasma collections. Serum SARS-CoV-2 (anti-S + anti-N) IgG and IgM, anti-S1 IgA and neutralizing titres titers (NTs) were measured. Results: Anti-SARS-CoV-2 antibody levels steadily decreased. No correlation was found between anti-S/anti-N IgG and IgM levels and viral NT, measured by either a microneutralization test or the surrogate RBD/ACE2-binding inhibition test. Conversely, NTs directly correlated with anti-S1 IgA levels. Hyperimmune donor plasma, administered to five SARS-CoV-2 patients with persistent, severe COVID-19 symptoms, induced short-term clinical and pathological improvement. Discussion: Reported data suggest that high NTs can persist longer than expected, thus widening hyperimmune plasma source, availability and potential use. In vitro RBD/ACE2-binding inhibition test is confirmed as a convenient surrogate index for neutralizing activity and patients’ follow-up, suitable for clinical settings where biosafety level 3 facilities are not available. IgA levels may correlate with serum neutralizing activity and represent a further independent index for patient evaluation.